Police and the Birth of the Governmentality in the Works of Michel Foucault - Marinković, Dušan; Ristić, Dušan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
Abstract: In this paper we research the meaning and significance of the concept of police in the works of Michel Foucault. We assume that this concept, whose emergence in Foucault's analytics is placed within the eighteenth century is different from the modern concept of police from nineteenth and twentieth century. Our hypothesis is that early concept of police was not a consequence of the single dispositive of power and the result of the sovereign type of power. We understand the Foucault's concept of police in the context of the birth of governmentality and historical appearance of the diagram of security, where dispositive of space is crucial. Foucault's police as the regulative practice of distribution of situational forces in society was a spatially regionalized and segmented, regulatory social mechanism. It occurs together with the processes of politicization of life, along with the emergence of biopolitical technologies. In this sense, police as the phenomenon of XVIII century, should be understood as the emergence of the new type of governmentality and regulation that will signify the important modulation in the disciplinary diagram and the appearance of the new type of reality – society.